Influence of prosthesis-related factors on the occurrence of early leaflet thrombosis after transcatheter aortic valve implantation. (26th June 2020) - Breitbart, Philipp; Pache, Gregor; Minners, Jan; Hein, Manuel; Schröfel, Holger; Neumann, Franz-Josef; Ruile, Philipp
Abstract: Aims: Early leaflet thrombosis (LT) is a well-described phenomenon after transcatheter aortic valve implantation (TAVI) with an incidence around 15%. Data about predictors of LT are scarce. The purpose of the study was to investigate the influence of prosthesis-related factors on the occurrence of LT. Materials and results: Fusion imaging of pre- and post-procedural computed tomography angiography was performed in 55 TAVI patients with LT and 140 selected patients as control groups (85 patients in an unmatched and 55 in a matched control) to obtain a 3D reconstruction of the transcatheter heart valve (THV) within the native annulus region. All patients received a balloon-expandable Sapien 3 THV. The THV length above and below the native annulus was measured within the fused images to assess the implantation depth. The deployed THV area was quantified on three heights (left ventricular outflow tract end, stent centre, and aortic end) to determine the average expansion of the prosthesis as percent of the nominal area. We also calculated the extent of prosthesis waist in percent of maximum area. After multivariate adjustment, the extent of THV waist [odds ratio (OR) per 10% (confidence interval, CI) 0.636 (0.526–0.769), P < 0.001] as prosthesis-related factor and previous oral anticoagulation [OR (CI) 0.070 (0.020–0.251), P < 0.001] had significant, independent influence on the occurrence of LT. The implantation depth showed no influence on LT manifestation ( P = 0.704). Conclusion: Besides the absence of previous oral anticoagulation, a less pronounced waist of the implanted THV was a prosthesis-position-related independent predictor of LT after TAVI using the Sapien 3.